PROPOSAL FOR A CLINICAL PROTOCOL FOR THE CONSERVATIVE TREATMENT OF URGE URINARY INCONTINENCE (Estima – Brazilian Journal of Enterostomal Therapy, 2023)
Objective: To present a proposal for a clinical protocol for the conservative treatment of urge urinary incontinence. Method: Experience report based on existing scientific evidence and clinical experience of authors who perform nursing consultations for people with urge urinary incontinence, outlined in accordance with the Brazilian Ministry of Health’s proposal for the elaboration of clinical protocols. Results: A clinical protocol was proposed with nursing diagnosis and interventions based on the North American Nursing Diagnosis Association (NANDA) and Nursing Interventions Classifications (NIC), with systematized steps to verify the presence of related factors or conditions associated with the diagnosis, namely: hyperactive pelvic floor, anxiety, constipation, urinary tract infection, low fluid intake, inadequate sanitary behavior, diabetes mellitus, pelvic organ prolapse, high consumption of potential bladder irritants and persistence of symptoms. Soon after, the actions that should be implemented by the nurse were described in detail. Conclusion: It is considered that the flow and detailing of the actions presented can be adopted by nurses in order to identify and treat people with urge urinary incontinence, thus minimizing the prevalence of the problem and promoting the quality of life of these people.